Revelations of ideology: apocalyptic class politics in early Roman Palestine - Keddie, Anthony ca. 20./21. Jh. (Supplements to the Journal for the study of Judaism, 2018)
"In Revelations of Ideology, G. Anthony Keddie proposes a new theory of the social function of Judaean apocalyptic texts produced in Early Roman Palestine (63 BCE-70 CE). In contrast to evaluations of Jewish and early Christian apocalyptic texts as "literature of the oppressed" or literature of resistance against empire, Keddie demonstrates that scribes produced apocalyptic texts to advance ideologies aimed at self-legitimation. By revealing that their opponents constituted an exploitative class, scribes generated apocalyptic ideologies that situated them in the same exploited class as their constituents. Through careful historical and ideological criticism of the Psalms of Solomon, Parables of Enoch, Testament of Moses, and Q source, Keddie identifies an internally diverse tradition of apocalyptic class rhetoric in late Second Temple Judaism" ...